Ecopolitics Podcast, Episode 2: Introduction to Ecopolitics - Katz-Rosene, Ryan (Université d'Ottawa | University of Ottawa, 2020)
In this episode, we speak with Dr. James Meadowcroft, Professor in both the School of Public Policy and Administration and in the Department of Political Science at Carleton University. He sheds some light on how the environment became a defining issue in the discipline of Political Science, and shares how an organization called the Transition Accelerator works to advance technological, business and social change for a more sustainable future. [Produced by Nicole Bedford; Artwork by Adam Gibbard; Transcription by Kika Mueller].